2005
DOI: 10.1091/mbc.e04-05-0438
|View full text |Cite
|
Sign up to set email alerts
|

NGF Controls Dendrite Development in Hippocampal Neurons by Binding to p75NTRand Modulating the Cellular Targets of Notch

Abstract: Notch and neurotrophins control neuronal shape, but it is not known whether their signaling pathways intersect. Here we report results from hippocampal neuronal cultures that are in support of this possibility. We found that low cell density or blockade of Notch signaling by a soluble Delta-Fc ligand decreased the mRNA levels of the nuclear targets of Notch, the homologues of enhancer-of-split 1 and 5 (Hes1/5). This effect was associated with enhanced sprouting of new dendrites or dendrite branches. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 42 publications
7
90
0
Order By: Relevance
“…In adult dorsal root ganglion neurons and postnatal cerebellar neurons, binding of myelinderived proteins to p75 NTR activates RhoA and thereby inhibits growth (Yamashita et al, 2002). Recent studies also suggest a multipotential role of p75 NTR in modulating dendrite morphology during development of hippocampal neuronal cultures, by either reducing the number of primary dendrites and by controlling the cellular targets of Notch (Salama-Cohen et al, 2005) or by mediating the filopodia growth promoting activity of TrkB-T1 (Hartmann et al, 2004). These and related observations suggest that the effects of p75 NTR strongly depend on the cellular context in which it is expressed and that, under certain cellular conditions, it can act antagonistically to the Trk receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In adult dorsal root ganglion neurons and postnatal cerebellar neurons, binding of myelinderived proteins to p75 NTR activates RhoA and thereby inhibits growth (Yamashita et al, 2002). Recent studies also suggest a multipotential role of p75 NTR in modulating dendrite morphology during development of hippocampal neuronal cultures, by either reducing the number of primary dendrites and by controlling the cellular targets of Notch (Salama-Cohen et al, 2005) or by mediating the filopodia growth promoting activity of TrkB-T1 (Hartmann et al, 2004). These and related observations suggest that the effects of p75 NTR strongly depend on the cellular context in which it is expressed and that, under certain cellular conditions, it can act antagonistically to the Trk receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that Notch activation mediates changes in gene expression responsible for the contact-dependent inhibition of dendritic growth. 42 Using primary murine hippocampal cultures, Salma-Cohen et al 43 provided evidence that NF-kB activation downstream of NGF and the p75 NTR can regulate expression of some of the same transcripts as Notch. This pathway was suggested to function in parallel to Notch, and to allow modulation of dendrite growth by soluble factors even in the absence of cell-contact signals.…”
Section: Growth Factor Signalingmentioning
confidence: 99%
“…Activated Notch receptor has been suggested to play a role in determining the only possible cell fate decision in postmitotic mature neurons, such as synaptic remodeling or neurite extension/retraction (Berezovska et al, 1999), as well as in the control of the branching points number according to the cell density and the specific cellular population (Sestan et al, 1999;Salama-Cohen et al, 2005). In the present study, we focused our attention on the varicosities, particular structures along the neurite that are believed to be hallmarks of the presynaptic compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Notch pathway also controls the postsynaptic compartment by regulating dendrite outgrowth and branching (Redmond et al, 2000). Recent studies showed that stimulation of Notch by cell-cell contact or neurotrophic factors affects dendrite morphology and the ratio of excitatory/inhibitory synaptic terminals in hippocampal cultured cells (Salama-Cohen et al, 2005. Moreover, excitotoxic stimuli induced Notch protein activation in adult brain; this observation suggested us the possible Notch pathway involvement in degenerative processes Grilli et al, 2003).…”
Section: Introductionmentioning
confidence: 99%